Sustainability of unemployment insurance policy in Brazil : contribution of human resource management and accounting - França, José Antonio de (2018)
Unemployment insurance, as a social policy instrument aims at reducing the temporal suffering of the families when the family income provider loses their job. In this context, we discuss the results of a research conducted in the first half of 2013 on the unemployment insurance policy in Brazil, whose purpose is to obtain an answer as to how the amount of unemployment insurance beneficiaries is related and associated with the economically active population (PEA) and the gross domestic product (GDP), in order to analyze and investigate the sustainability of this policy from the fluctuations of the economically active population and the GDP. The methodology uses descriptive and quantitative techniques. The results show that the number of beneficiaries of unemployment insurance in Brazil, concomitantly, also grows when the GDP and the economically active population grow, revealing evidence of lack of sustainability, for a sustainable policy should have an inverse association.